2018
DOI: 10.1021/acs.accounts.8b00397
|View full text |Cite
|
Sign up to set email alerts
|

Development of Mannopyranoside Therapeutics against Adherent-Invasive Escherichia coli Infections

Abstract: Conspectus Preventing bacterial adhesion to host cells is a provocative and alternative approach to traditional antibiotic treatments given the increasing microbial resistance. A brief overview of common antibiotic treatments is described in light of their respective resistance and remaining susceptibility. This strategy has been seriously considered in the context of adherent-invasive infections in Crohn’s disease and urinary tract infections in particular. The adhesions of various pathogenic Escherichia coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 59 publications
0
41
0
Order By: Relevance
“…UPEC adhesion relies mainly on the interaction between FimH and mannosylated uroplakin proteins on the luminal surfaces of urothelial cells as well as other cellular receptors such as integrins [1,5,8,[13][14][15]. Therefore, FimH antagonists, such as d-mannose, have gained increasing consideration and proven to be effective for the treatment and/or prevention of acute and recurrent UPEC-mediated UTIs [21,22,[24][25][26][27]. Furthermore, d-mannose represents a real alternative to antibiotic regimens, reducing the burden of antibiotic resistance and associated side effects [2,14,31,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UPEC adhesion relies mainly on the interaction between FimH and mannosylated uroplakin proteins on the luminal surfaces of urothelial cells as well as other cellular receptors such as integrins [1,5,8,[13][14][15]. Therefore, FimH antagonists, such as d-mannose, have gained increasing consideration and proven to be effective for the treatment and/or prevention of acute and recurrent UPEC-mediated UTIs [21,22,[24][25][26][27]. Furthermore, d-mannose represents a real alternative to antibiotic regimens, reducing the burden of antibiotic resistance and associated side effects [2,14,31,[34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, molecules able to interfere with bacterial virulence mechanisms have been proposed to combat UPEC infections [20]. Accordingly, FimH antagonists, such as d-mannose and its derivatives, have emerged as anti-virulence therapeutic strategies for the treatment of UTIs [21][22][23][24][25][26][27]. d-mannose, a C-2 epimer of d-glucose, as well as d-mannose-analogs, prevent FimH-mediated bacterial adhesion through a competitive inhibition mechanism [18,21,22,24,28].…”
Section: Introductionmentioning
confidence: 99%
“…Para-substituted biphenyl derivatives were shown to be particularly appealing, owing to their numerous favorable binding interactions within the tyrosine gate. Thus, the structural and functional analyses of a series of O-, C-, and S-linked mannoside derivatives, incorporating the 1,1′-biphenyl pharmacophore and diverse aglycone atoms, demonstrated the suitability of these antagonists, establishing the possibility of further exploring these chemically modified mannosides [ 101 , 102 ]. Furthermore, it was shown that the biphenyl group linked to mannosides can be efficiently absorbed if orally administered [ 54 , 88 ].…”
Section: Fimh Antagonists Biochemical Characteristics and Bioavaimentioning
confidence: 99%
“…The FimH bacterial lectins adhere to the highly mannosylated glycoprotein uroplakin 1a [9,10] on the bladder cells and on glycoprotein 2 (GP2) exclusively expressed in the small intestine [7,11]. Once the infection process is initiated, it is usually followed by thick biofilm formation [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Given that bacterial adhesion to host cells is the preliminary step toward the release of toxic proteins, the design of potent E. coli FimH antagonists has been the target of several efforts [15,16]. Several glycomimetic analogs of the naturally occurring complex oligomannosides have been synthesized [8,10] that provided potent α-D-mannopyranoside-based antiadhesins. Since small molecule antagonists represent the foremost choice of the pharmaceutical industry, these glycomimetics constitute most promising candidates for the replacement of the natural lead oligomannosides onto which E. coli adhere to [10,17].…”
Section: Introductionmentioning
confidence: 99%